2010
DOI: 10.1111/j.1447-0756.2009.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality and cesarean delivery: An analytical observational study

Abstract: CD is increasingly perceived as a low-risk procedure. However, the present study clearly demonstrates that the risk of maternal death due to CD is significantly high, particularly when performed in labor. Therefore, CD should only be practiced when conditions clearly demand it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 14 publications
3
31
0
8
Order By: Relevance
“…This method allowed us to assess the excess maternal and neonatal mortality risks related to CS in all the patients except very high risk women, and to provide results which could be generalizable to all women delivering in referral hospitals in similar contexts without life threatening maternal and fetal compromise. Furthering this approach, we performed a sensitivity analysis including only low-risk women (i.e., with no identifiable medical risk factors) as proposed by authors from more developed countries [2], [3], [17], [18], and we obtained similar results. We did not have information available for congenital malformations and anomalies, which are known to be associated with poor perinatal outcomes.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This method allowed us to assess the excess maternal and neonatal mortality risks related to CS in all the patients except very high risk women, and to provide results which could be generalizable to all women delivering in referral hospitals in similar contexts without life threatening maternal and fetal compromise. Furthering this approach, we performed a sensitivity analysis including only low-risk women (i.e., with no identifiable medical risk factors) as proposed by authors from more developed countries [2], [3], [17], [18], and we obtained similar results. We did not have information available for congenital malformations and anomalies, which are known to be associated with poor perinatal outcomes.…”
Section: Discussionmentioning
confidence: 63%
“…If residual confounding cannot be excluded, it is unlikely that it might explain the magnitude of the excess risks we estimated for CS and operative vaginal delivery compared to spontaneous vaginal delivery. In addition, the odds ratios we calculated were of the same level as those reported in other recent studies [1][3].…”
Section: Discussionmentioning
confidence: 80%
“…We recently conducted a study at a university hospital in Tanzania that revealed a sharp increase in CS rates between 2000 and 2011, and found the rise was accompanied by a significant increase in the maternal mortality ratio (MMR) [15]. Several studies have reported increased risk of blood transfusion [16, 17], hysterectomy [16, 17], bleeding complications [18], infections [18], and maternal death [13, 16, 17, 19] among women undergoing CS. However, assessing the risks of CS versus vaginal birth is complicated, as adverse outcomes after CS might be confounded by the medical condition that lead to the operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, assessing the risks of CS versus vaginal birth is complicated, as adverse outcomes after CS might be confounded by the medical condition that lead to the operation. There are few publications with ideal study design to establish the causal relationship between CS and maternal morbidity and mortality [17, 19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…(Ash et al 2007;AWMF 2010c;Blanchette et al 2011;Chiu et al 2013;Ecker et al 2007; A c c e p t e d M a n u s c r i p t Getahun et al 2006;Greene et al 1996;Hemminki et al 1997;Kamilya et al 2010;Lee et al 2008;Liu et al 2007;Nawroth 2013;O`Neill et al 2013).…”
Section: Why Is (Emergency) Surgery That Used To Be Performed For Purmentioning
confidence: 95%